Biomechanics and tennis. Issue 5 (21st April 2006) - Elliott, B
Abstract : Success in tennis requires a mix of player talent, good coaching, appropriate equipment, and an understanding of those aspects of sport science pertinent to the game. This paper outlines the role that biomechanics plays in player development from sport science and sport medicine perspectives. Biomechanics is a key area in player development because all strokes have a fundamental mechanical structure and sports injuries primarily have a mechanical cause.